2015
DOI: 10.1111/php.12438
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Ureaplasma urealyticum to Methylene Blue‐Mediated Photodynamic Antimicrobial Chemotherapy: An in vitro Study

Abstract: The aim of this study was to detect the susceptibility of Ureaplasma urealyticum to methylene blue-mediated photodynamic antimicrobial chemotherapy (PACT). Three U. urealyticum strains including the standard serotype 1 and 5, and a clinically collected strain were used in this study. Strains were first incubated in 96-well culture plates in the presence of methylene blue with decreasing concentrations (from 1 to 0.015625 mg mL(-1)) for 20 or 60 min, and then submitted to irradiation with a light-emitting diode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The tested microorganisms were mostly obtained from American Type Culture Collection but in some cases pathogens, especially S. aureus , were isolants or clinical strains (Table 1). 60,195,210,211,251,363,421,461 Several studies focused on APDT of oral microflora, in particular, bacteria found in dentin, usually isolated from patients with deep caries lesions 153,216,257,263,282,284,362,385…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tested microorganisms were mostly obtained from American Type Culture Collection but in some cases pathogens, especially S. aureus , were isolants or clinical strains (Table 1). 60,195,210,211,251,363,421,461 Several studies focused on APDT of oral microflora, in particular, bacteria found in dentin, usually isolated from patients with deep caries lesions 153,216,257,263,282,284,362,385…”
Section: Resultsmentioning
confidence: 99%
“…The tested microorganisms were mostly obtained from American Type Culture Collection but in some cases pathogens, especially S. aureus, were isolants or clinical strains (Table 1). 60,195,210,211,251,363,421,461 Several studies focused on APDT of oral microflora, in particular, bacteria found in dentin, usually isolated from patients with deep caries lesions 153,216,257,263,282,284,362,385 Some studies also investigated MB-APDT targeted towards viruses, including vesicular stomatitis virus (VSV), bovine viral diarrhea virus (BVDV), dengue virus, West Nile virus (WNV), hepatitis C virus (HCV), herpes simplex virus type 1 (HSV-1) and SARS-CoV2. 215,297,299,300,311,314,321,331,403,408,409,411 Anti-parasitic photodynamic therapy investigations were dominated by Leishmania spp.…”
Section: The Targets Of Methylene Blue-mediated Antimicrobial Photoin...mentioning
confidence: 99%